2017
DOI: 10.1016/j.ijpharm.2017.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Ligand peptide-grafted PEGylated liposomes using HER2 targeted peptide-lipid derivatives for targeted delivery in breast cancer cells: The effect of serine-glycine repeated peptides as a spacer

Abstract: Ligand peptide-grafted PEGylated liposomes have been widely studied for targeted drug delivery systems. Because ligand peptides are commonly grafted using PEG as a spacer on the surface of PEGylated liposomes, the interaction between ligand peptides and their corresponding receptors can be interrupted by steric hindrance of the PEG layer. Therefore, we aimed to develop ligand peptide-lipid derivatives to enhance the targeting efficiency of ligand peptide-grafted PEGylated liposomes, and designed a new ligand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…To deliver nanoparticles to specific tissues and cells, ligand modification is a rational strategy. Recently, we have reported high functionality and quality (HFQ) lipids for the preparation of ligand-targeted PEGylated liposomes and demonstrated the advantage of using a serine-glycine repeats (SG)5 spacer for efficient peptide ligand presentation on the liposomal surface [22]. This technique is simple and versatile because HFQ lipids are post-inserted into the 6 liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…To deliver nanoparticles to specific tissues and cells, ligand modification is a rational strategy. Recently, we have reported high functionality and quality (HFQ) lipids for the preparation of ligand-targeted PEGylated liposomes and demonstrated the advantage of using a serine-glycine repeats (SG)5 spacer for efficient peptide ligand presentation on the liposomal surface [22]. This technique is simple and versatile because HFQ lipids are post-inserted into the 6 liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…The KWSY sequence was, in this study, modified from KCCYSL, a well-known ErbB2-targeting motif. KCCYSL was identified as an ErbB2-binding peptide through phage-display screening [25], and was used for cancer imaging agents and delivery tools to target ErbB2-expressing cells [10][11][12]26]. In this study, direct coupling of KCCYSL with the MTD was not satisfactory because high amounts of KCCYSL:MTD were needed to kill the ErbB2-high-expressing FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we compared the uptake pathways taken by various Rn and NuBCP-9-Rn conjugates in a Bcl-2 overexpressing cell line, MDA-MB-231 (human breast cancer cells). 17,18) We found that NuBCP-9-R12 and NuBCP-9-R14 conjugates resulted in severe non-specific cytotoxicity. Based on our results, NuBCP-9-R10 conjugate was concluded to be a good compound for inducing apoptosis through Bcl-2 in cancer cells while resulting in a tolerable degree of non-specific cytotoxicity.…”
mentioning
confidence: 89%